On the Comparison of the Therapeutic Effects of Matrix Treatment on Severity of Addiction and Mental Health between Female and Male Methamphetamine Abusers - roholla hadadi; nafiseh motlagh; zeinab kamali; shahnaz mohamadi; ghasem keshavarz; sepideh bakht (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study was an attempt to compare the therapeutic effects of matrix treatment on the severity of addiction and mental health between female and male methamphetamine abusers. Method: From among 121 patients admitted in maintenance treatment centers, 91 patients who met the conditions required for participation in this study were selected and randomly assigned to two separate groups based on gender (female=43 and male=48). In the following, 9 males and 4 females were excluded from the study. Mental Health and Addiction Severity Index was administered to both groups before and after the intervention. Results: The results were indicative of no significant difference in any of the subscales of addiction severity between female and male abusers after treatment. However, the difference in mental health scores was statistically significant. Males experienced an increase in depression in comparison with females whereas females underwent higher levels of anxiety than males. Conclusion: Matrix treatment shows significantly different effects on mental health of females and males.